A GIS policy approach for assessing the effect of fertilizers on the quality of drinking and irrigation water and wellhead protection zones (Crete, Greece). (15th March 2017) - Kourgialas, Nektarios N.; Karatzas, George P.; Koubouris, Georgios C.
Abstract: Fertilizers have undoubtedly contributed to the significant increase in yields worldwide and therefore to the considerable improvement of quality of life of man and animals. Today, attention is focussed on the risks imposed by agricultural fertilizers. These effects include the dissolution and transport of excess quantities of fertilizer major- and trace-elements to the groundwater that deteriorate the quality of drinking and irrigation water. In this study, a map for the Fertilizer Water Pollution Index (FWPI) was generated for assessing the impact of agricultural fertilizers on drinking and irrigation water quality. The proposed methodology was applied to one of the most intensively cultivated with tree crops area in Crete (Greece) where potential pollutant loads are derived exclusively from agricultural activities and groundwater is the main water source. In this region of 215 km 2, groundwater sampling data from 235 wells were collected over a 15-year time period and analyzed for the presence of anionic (ΝΟ −3, PO −3 4 ) and cationic (K +1, Fe +2, Mn +2, Zn +2, Cu +2, B +3 ) fertilizer trace elements. These chemicals are the components of the primary fertilizers used in local tree crop production. Eight factors/maps were considered in order to estimate the spatial distribution of groundwater contamination for each fertilizer element. The eight factors combined were used to generate the Fertilizer Water Pollution Index (FWPI) map indicating the areas with drinking/irrigation water pollution due to the high groundwater contamination caused by excessive fertilizer use. Moreover, by taking into consideration the groundwater flow direction and seepage velocity, the pathway through which groundwater supply become polluted can be predicted. The groundwater quality results show that a small part of the study area, about 8 km 2 (3.72%), is polluted or moderately polluted by the excessive use of fertilizers. Considering that in this area drinking water sources (wells) are located, this study highlights an analytic method for delineation wellhead protection zones. All these approaches were incorporated in a useful GIS decision support system that aids decision makers in the difficult task of protection groundwater resources. Graphical abstract: Highlights: National policy system for assessing groundwater quality status, a case study in one of the most intensively cultivated area of Greece. Development of a Fertilizer Water Pollution Index (FWPI). Monitoring drinking and irrigation wells data. Estimation of groundwater flow direction and seepage velocity. Accurate delineation of wellhead protections zones.